The potential of Trichoderma asperellum for degrading wheat straw and its key genes in lignocellulose degradation - Zhu, Qijun; Liu, Weiwei; Song, Liye; Guo, Zhenzhen; Bian, Zhiyao; Han, Yunsheng; Cai, Hongying; Yang, Peilong; Meng, Kun (Frontiers in Microbiology, 2025)
This study explored Trichoderma asperellum’s lignocellulose degradation potential in wheat straw (WS) and NaOH-treated WS via solid-state fermentation (SSF) over 30 days. Compared to the control, WS treated with T. asperellum (TW) and NaOH-treated WS with T. asperellum (TN) showed increased dry matter loss rates of 15.67 and 15.76%, respectively. Cellulose degradation reached 33.51 and 28.00%, while hemicellulose degradation increased to 31.56 and 63.86%. Crude protein (CP) content rose to 10.96 and 7.44%, and reducing sugar content to 10.86 and 12.41 mg/g, respectively. T. asperellum effectively reduced lignocellulose content and enhanced substrate nutrition, supporting subsequent uses of WS as fertilizer, feed, or for bioethanol production. Enzymatic activity and structural analyses were performed to further confirm the lignocellulose-degrading ability of T. asperellum and to analyze the degradation mechanisms. Transcriptomic analysis revealed that, compared with the control group, the TN group had 4,548, 4,399, and 6,051 differentially expressed genes (DEGs) at 5, 10, and 30 days, respectively, mainly involved in cellulose and hemicellulose degradation, carbohydrate metabolism, carbohydrate transport, glycoside hydrolases, and polysaccharide binding. T. asperellum can modify lignin by expressing dye-decolorizing peroxidase genes, and multiple key genes were identified for further research into its genetic regulation in lignocellulose degradation.